Validation by experts of Risk of suicide Nursing Diagnosis in the elderly - Girliani Silva de Sousa; Jaqueline Galdino Albuquerque Perrelli; Suzana de Oliveira Mangueira; Everton Botelho Sougey
ABSTRACT Objective: to validate the conceptual and operational definitions content of factors for Risk of suicide Nursing Diagnosis in the elderly. Method: this is validation of the conceptual and operational definitions content of factors for Risk of suicide in the elderly, performed by 15 experts, from November 2015 to March 2016. Risk factors were classified into three hierarchical chuncks. The data were analyzed by descriptive statistics and binomial test. Results: of the 54 validated risk factors, only eight presented problems regarding clarity, simplicity and accuracy: chronic pain, vision problems, retirement, frustration, medication neglect and depression. Only rigidity was not validated as relevant for the study diagnosis. Conclusion: content validation of the risk factors for Nursing Diagnosis can guide the clinical practice of the nurse in the early detection of risk of suicide in the elderly.